Foley catheter with vaginal prostaglandin E2 gel versus vaginal prostaglandin E2 gel alone for induction of labour: a randomized controlled trial - Garg, Ruchika; Vardhan, Shailza; Singh, Saroj; Singh, Richa (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Induction of labour is significant when continuing pregnancy possess adverse effect on health of mother and her unborn baby. Different methods have been used for induction of labour. At present there is very less literature regarding simultaneous use of Foleys catheter and PGs. The present study was done to compare the efficacy of using intracervical Foleys catheter and PGE2 gel simultaneously versus PGE2 gel alone for induction of labour. Methods: Prospective study, conducted in department of obstetrics and gynaecology for duration of 6 months. 100 women requiring induction of labour were included in the study and were randomly divided into two groups. 50 women were included in group A (simultaneous use of intracervical Foley catheter with PGE2 gel) and 50 women were included in Group B (intravaginal insertion of PGE2 gel only). Results: Maternal age, gestation age, parity, indication of induction and primary Bishops score were comparable in both the groups. Mean induction to active phase interval in both groups which was 5.8±0.80 hours in Group A and 6.23±0.40 hours in Group B. Also mean time taken from induction to delivery in Group A was 10.08±5.6 hours and in Group B was 14.6±6.9 hours which was significantly less in Group A. The rate of vaginal delivery in group A and Group B was 66% and 58% respectively which was slightly more in Group A but was not significant. Conclusions: In the present study we conclude that simultaneous use of mechanical method with Foleys catheter and PGE2 gel is better and more effective method for induction of labour than PGE2 alone. However, large sample size is required to reach more confirmatory results.